# Solve the following initial value problems. y' 1 = -y 1 - y 2 y' 2 = y 1 – y 2 y 1 (0) = 1, y 2 (0) = 0

Chapter 4, P R O B L E M S E T 4 . 3 #14

Solve the following initial value problems.

y'_{1} = -y_{1 }- y_{2}

y'_{2} = y_{1} – y_{2}

y_{1}(0) = 1, y_{2}(0) = 0

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

**Related Book For**

P R O B L E M S E T 4 . 3:

- PROBLEMSET4.3-1
- PROBLEMSET4.3-2
- PROBLEMSET4.3-3
- PROBLEMSET4.3-4
- PROBLEMSET4.3-5
- PROBLEMSET4.3-6
- PROBLEMSET4.3-7
- PROBLEMSET4.3-8
- PROBLEMSET4.3-9
- PROBLEMSET4.3-10
- PROBLEMSET4.3-11
- PROBLEMSET4.3-12
- PROBLEMSET4.3-13
- PROBLEMSET4.3-15
- PROBLEMSET4.3-16
- PROBLEMSET4.3-17
- PROBLEMSET4.3-18
- PROBLEMSET4.3-19
- PROBLEMSET4.3-20

P R O B L E M S E T 4 . 4:

P R O B L E M S E T 4 . 5:

PROBLEM SET 4.6: